2015
DOI: 10.1007/s00226-015-0700-5
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of balsa (Ochroma pyramidale) wood

Abstract: Balsa, with its low density and relatively high mechanical properties, is frequently used as the core in structural sandwich panels, in applications ranging from wind turbine blades to racing yachts. Here, we describe both the cellular and cell wall structure of balsa, to enable multi-scale modelling and an improved understanding of its mechanical properties. The cellular structure consists of fibers (66-76%), rays (20-25%) and vessels (3-9%). The density of balsa ranges from roughly 60 to 380 kg/m 3 ; the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 29 publications
7
134
0
1
Order By: Relevance
“…Previous results on samples of oak wood from the Swedish warship Vasa (Svedström et al, 2012) showed similar crystallinity values while those of balsa (Ochroma pyramidale) (Borrega et al, 2015) were much higher. Small differences in the sample crystallinity values between the bamboo species can also be due to the differences in the orientation distribution of the cellulose microfibrils and might not be an independent result.…”
Section: Nanoscale: Nanoindentation Chemical Composition X-ray Scatmentioning
confidence: 59%
“…Previous results on samples of oak wood from the Swedish warship Vasa (Svedström et al, 2012) showed similar crystallinity values while those of balsa (Ochroma pyramidale) (Borrega et al, 2015) were much higher. Small differences in the sample crystallinity values between the bamboo species can also be due to the differences in the orientation distribution of the cellulose microfibrils and might not be an independent result.…”
Section: Nanoscale: Nanoindentation Chemical Composition X-ray Scatmentioning
confidence: 59%
“…The thickness of the double cell wall is about 4 µm in vessels, 0.9 µm in rays, and between 0.8 µm and 3 µm in fibers, increasing with density (Easterling et al 1982;Da Silva & Kyriakides 2007;Borrega et al 2014). …”
Section: Structure and Composition Of Balsa Woodmentioning
confidence: 98%
“…The cellular structure in balsa wood consists of fibers (66-76%), rays (20-25%) and vessels (3-9%) (Borrega et al 2014). The vessels are long tubular structures that run axially along the trunk of the tree and transport fluids from the roots to the crown.…”
Section: Structure and Composition Of Balsa Woodmentioning
confidence: 99%
See 2 more Smart Citations